Tips for Choosing a College Major that Suits your Interests and Talents - Anita Candra Dewi; Nur Arif Pradana; Hermit Ian Nurfatila; Achsan; Dwi Paski Maulidya; Juwita Hamsar (MultiTech Publisher, 2023)
Education is the delivery of individuals towards a better future. High school students are in the age range of 15-18 years. This article aims to provide education to high school students who will continue their education to college so that they do not make mistakes in choosing their majors and according to their interests and talents. Seek detailed information about the major of interest. The ways to choose a major are (1) Realising that the chosen major is only one of the initial steps of the career achievement process. (2) The chosen major should be in accordance with your abilities and interests. (3) Think far ahead to see the consequences of each choice.